Bioethics in the education of the future healthcare professionals - Vidin Kirkov; Alexandrina Vodenicharova; Krasimira Markova; Lyudmila Borisova; Kristina Popova (Pensoft Publishers, 2024)
Background: Ensuring and maintaining the quality of higher medical education is of strategic importance to society, bearing in mind that is producing competent medical personnel who will conduct health care activities with a view any decision in medical practice to be based both on evidences and values. Bioethics case studies are intended to be a useful training tool to help medical students in their future daily practice as doctors and contribute to improving doctor-patient relationships and team work. Methods: A questionnaire survey was distributed among the medical students of Medical University - Sofia, included 640 students in 4, 5 and 6 years of their study. It analyses the necessity of learning the Universal Declaration on Bioethics and Human Rights, approved on the 19th of October 2005 by the UNESCO General Assembly. Results: About ½ of the participants in the empirical study, to varying degrees, were not familiar with the bioethical principles of UNESCO Universal Declaration on Bioethics and Human Rights. A large proportion of respondents gave affirmative responses about the importance of ethical knowledge in their future medical practice. According to the respondents, training in Bioethics and Human Rights will increase their ethical competence as medical professionals. Conclusions: The results of the empirical study give us grounds to make recommendations to the responsible institutions to update and reorganize the undergraduate internship of medical students by including the discipline of Medical Ethics and the Universal Declaration on Bioethics and Human Rights.